CONSUMER EVALUATION RELATED TO SIMILIARITY, BRAND REPUTATION, PERCIVED RISK, AND CUSTOMER INNOVATIVENESS ON BRAND EXTENSION OF THE LION AIR GROUP - Thomas Aquinas Radito; Kunto Wibisono; Dewi Puspitasari; Anwar Azmi Hidayatullah (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study examines the influence of consumer evaluations regarding similiarity, brand reputation, perceived risk, and customer innovativeness on the brand extension of the Lion Air Group. The population studied is all people who use airlines which are brand extensions of the Lion Air Group, which consists of Lion Air, Wings Air, Batik Air, and Super Air Jet. The sample used in this study was 250 respondents. The hypothesis was tested using multiple regression. The regression results show that consumer evaluations regarding similiarity and customer innovativeness have proven to have a significant effect on the brand extension of the Lion Air Group. Meanwhile, consumer evaluations regarding brand reputation and perceived risk have not been shown to significantly influence the brand extension of the Lion Air Group.